TECHNOLOGY ADOPTION AND TECHNICAL EFFICIENCY OF OIL PALM SMALLHOLDER PLANTATION IN RIAU AND WEST KALIMANTAN - Anto Ariyanto; Yusman Syaukat; Sri Hartoyo; Bonar M. Sinaga (Jurnal Manajemen & Agribisnis, 2020)
This study was conducted to assess the role of adoption of oil palm cultivation technology that has been recommended by the government (RI Regulation of the Minister of Agriculture No 131 / Permentan / OT.140 / 12/2013 concerning Guidelines for Good Oil Palm Cultivation) on production efficiency from smallholder plantations on the dependent smallholder and independent smallholder in Riau and West Kalimantan. Specifically, this study is: (1) to analyze the factors that influence the level of production and analyze the technical efficiency of smallholder oil palm in Riau and West Kalimantan, (2) to analyze the effect of intensity of technology adoption on productivity and efficiency of smallholder oil palm production in Riau and West Kalimantan, (3) To identify the factors affecting technical inefficiency in smallholder plantations in Riau and West Kalimantan. The research objectives were analyzed by using a stochastic frontier model to estimate productivity, the level of technical efficiency, and producer inefficiency simultaneously with allocative efficiency and economic efficiency. The results showed that smallholder oil palm farmers who adopt all recommended technologies compared to farmers who adopt not all recommended technologies had higher production efficiency. Analysis of technical efficiency showed that farmers in the dependent smallholder were more technically efficient than independent smallholders. Farmers who adopt more technology and had more experience, had higher efficiency than others. Farmers who were often associated with extension workers and more experience had higher efficiency than others. Keywords: oil palm smallholder, technology adoption, technical efficiency, Riau, West Kalimantan